Audit of IT Governance in the Field of Resource Management at the North Sumatra Investment and Licensing Service Office Based on the COBIT 5 Framework - Ilka Zufria (IJISTECH (International Journal of Information System and Technology), 2020)
At present, information technology is an important part for companies to meet their needs and support the achievement of strategic plans for the company. Providing competitive advantage, increasing effectiveness, time, and reducing expenses is the role of information technology that is very vital in today's business trade. By researching information technology governance using the COBIT 5 Framework in a company, it can be seen whether the company has met the requirements of the C indicators. In this study, we discussed resource management audits at the North Sumatra One-Stop Integrated Investment and Licensing Service Office to find out these capability indicators and have obtained results by conducting interviews using questionnaires distributed online to employees at the Service. With this research, we found that some indicators do not meet the capability of a company.